The species of Psomizopelma Gibson (Hymenoptera: Eupelmidae) - Gibson, Gary A. P. (Zootaxa, 2018)
The species of the New World genus Psomizopelma Gibson (Hymenoptera: Chalcidoidea: Eupelmidae: Eupelminae) are revised. Five species are recognized, including one species with macropterous females, P. macropterum n. sp. (♀: Belize, Bolivia, Brazil, Colombia, Costa Rica, Ecuador, French Guiana, Panama, Trinidad), and four species with brachypterous females, P. albiclava n. sp. (♀ ♂: Brazil), P. brachypterum Gibson, 1995 (♀ ♂: USA, Florida), P. fuscum n. sp. (♀: Dominican Republic), and P. metallicum n. sp. (♀: USA, Florida). The species are illustrated through macrophotography and keyed.